Good self, bad self: The Struggle in Shelley - Wroe, Ann (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractAlthough he sometimes decried the notion of a duality of body and soul, few poets were more conscious than Percy Bysshe Shelley of the soul’s imprisonment in the illusory material world. In considering Shelley’s notion of the self, this essay will track his constant search to discover and unlock his own inner powers of empathy, imagination and liberation.